A study of the cost and revenue in the production of different strains of hybrid broilers in Malaysia - Wolf, M.; Mukherjee, T. K.; Syed Jalaluddin, (Faculty of Agriculture, University of Malaya, 1976)
A study on the actual cost and revenue from five strains of commercial hybrid broilers (A, B, C, D and E) placed under different dietary levels of protein revealed that the nett profit is highest in strains A, B and C when the birds received the normal level of 24% and 20% protein in their starter's and finisher's ration respecitvely. Strains D and E showed highest nett profits when these birds received lower and higher levels of protein respectively suggesting variable protein requirements for different types of hybrid broilers. It was, however, noted that although the cost of producing the commercial hybrid broilers is higher than the locally produced crossbred broilers, yet the average nett profit from these commercial broilers increases by about 6.8% compared to the nett profit obtained from local-crossbreds.